Flavonóides e floroglucinóis de Harpalyce brasiliana Benth: aspectos químicos, biológicos e espectroscópicos - Araújo, Renata Mendonça (2008)
This work describes the phytochemical study of leaves, hartwood and roots of Harpalyce brasiliana, a plant commonly found in Ceará, Piauí and Maranhão States, where is popularly known as "raiz-de-cobra". Chromatographic treatment of the ethanol extract from roots led to the isolation and purification of the new 7,3',4'-tri-hydroxy-6-(3",7"-dimethylocta-2",6"-dienoyl)-flavanone (I), and eight pterocarpans: the known harpalicin I (II), maackiain (III), medicarpina (VI), cabenegrin A-I (V), cabenegrin A-II (VI), 2-geranyl-3- hydroxy-8,9-methylenedioxy-pterocarpan (VII), 2',3'-dehydrocabenegrin A-II (VIII) and the new 2-geranyl-3-hydroxy-8,9-methylenedioxy-pterocarpan (XI). Chromatography of the ethanol extract from heartwood yielded the pterocarpans medicarpina (VI), edunol (X) and the new 6a, 11a-di-hydro-2-(4 ',5'-dimethyl-pent-2'-enoyl)-3-hydroxy-9-methoxy-6Hbenzofuran[3,2-c]benzopirano (XI). From the ethanol extract of the leaves, the flavonoids quercetina (XII), orientin (XIII), 5,7-di-hydroxy-3 ',4'-methylenedioxy-isoflavone (XVI) and 5,3 "-di-hydroxy-3 ',4'-methylenedioxy-7,8:6",5""-2",2"-dimethylpiranisoflavone (XV) were isolated from the polar fraction. In addition, seven new phloroglucinols monomeric derivatives 1-hexanoyl-2',4,6-tri-hydroxy-3'-methyl -3'-(4-methyl-3-pentenyl)- benzopirano (XVI), 1-hexanoyl-2',4,6-tri-hydroxy-3'-methyl-3'-(4-methyl-4-hydroxy-3- pentenyl)-benzopiran (XVII), 1-hexanoyl-2',4,6-tri-hydroxy-3'-methyl-3'-(4-methyl-4- peroxyl-2-pentenyl)-benzopiran (XVIII), 1-hexanoyl-[2',3']-furan-3'-methyl-5'-(2-methylpropenyl)-4,6-di-hydroxy-benzopiran (XIX), 1 -hexanoyl- [2 ' ,3']-piran-3'-methyl-6'- [hydroxy-dimethyl-methyl]-4,6-di-hydroxy-benzopiran (XX) and two diastereoisomerics of the 1-hexanoyl-2',4,6-tri-hydroxy-3'-methyl-3'-(3-hydroxy-4-methy1-4-pentenyl)- benzopiran (XXI e XXII) were isolated, from the non-polar fraction of this extract. The pterocarpans harpalicin I and 2-geranyl-3-hydroxy-8,9-methylenedioxy-pterocarpan showed significant tripanocidal activity against epimagoste forms of Tripanossoma cruzi, and the 7,3',4'-trihydroxy-6-(3",7"-dimethyl-octa-2",6"-dienoyl)-flavanone and 2-geranyl- 3 -hydroxy-8,9-methylenedioxy-pterocarpan were active in tests for cytotoxicity against tumor cell lines in cultures. The structural characterization of the isolated compounds was performed through the spectroscopic methods IR, GC/MS and mainly NMR, including uni and bidimensional pulse sequences, and comparison with data from literature.